Assessment of other‐cause mortality in localized renal cell carcinoma patients within 15 years: A population‐based analysis. Issue 7 (18th August 2020) - Pecoraro, Angela; Knipper, Sophie; Palumbo, Carlotta; Rosiello, Giuseppe; Luzzago, Stefano; Tian, Zhe; Shariat, Shahrokh F.; Saad, Fred; Briganti, Alberto; Fiori, Cristian; Porpiglia, Francesco; Karakiewicz, Pierre I.
Abstract: Background and Objective: Five‐year other cause mortality (OCM) after nephrectomy for non‐metastatic renal cell carcinoma (RCC) should be marginal in properly selected surgical candidates. We examined 5‐year OCM rates as a quality of care indicator for patient selection. Materials and Methods: Within the Surveillance, Epidemiology, and End Results database (1997‐2011), we identified 59267 RCC patients treated with either radical (n = 27 804, 46.9%) or partial nephrectomy (n = 31 463, 53.1%). Temporal trends and multivariable Cox regression analyses assessed 5‐year OCM. Data were stratified according to age group, year of diagnosis, race, marital status, gender, and socio‐economic status. The overall OCM rates for the entire cohort at 5 years of follow‐up was 4.7% and decreased from 9.4% to 5.6% over the study span (−3.8%, P  < .001). The greatest decrease in 5‐year OCM rates over time was recorded in patients >70 years (17.0%‐9.6%, slope, −0.6%/y), as well as in African‐Americans (12.0‐6.2%; slope, −0.3%/y) and in males (8.9%‐4.7%; slope, −0.3%, all P  < .001). Conclusions: An important OCM decrease was recorded over the study span. Nonetheless, further improvement may be accomplished, especially in African‐Americans, unmarried and older individuals, who exhibited higher OCM rates than others. These three groups may represent ideal targets for better patient selection based on OCM considerations.